2020
DOI: 10.3390/ani10040640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microencapsulated Blend of Organic Acids and Essential Oils as a Feed Additive on Quality of Chicken Breast Meat

Abstract: Simple Summary: Chicken meat is largely consumed around the world, with an increasing demand in recent years. Unfortunately, chicken meat is very susceptible to oxidative deterioration; therefore, poultry industries often use synthetic dietary additives to improve meat shelf-life. However, due to the public's growing concern about the potential toxic effect of the synthetic additives, there is an increasing interest in natural antioxidant compounds. Among these, organic acids and essential oils could represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
(73 reference statements)
0
9
0
1
Order By: Relevance
“…They were reared on a comminute straw-litter with free access to feed and water, administered by nipple drinkers and plastic feeders. The feed program follows four different growth phases, consisting of starter (0–12 days), grower 1 (13–26 days), grower 2 (27–35 days), and finisher (36–46 days), as reported by Stamilla et al [ 18 , 19 ]. Feed texture ranged from finely grounded to crumble in the first 15 days and granulated from day 15 till the end of the cycle.…”
Section: Methodsmentioning
confidence: 99%
“…They were reared on a comminute straw-litter with free access to feed and water, administered by nipple drinkers and plastic feeders. The feed program follows four different growth phases, consisting of starter (0–12 days), grower 1 (13–26 days), grower 2 (27–35 days), and finisher (36–46 days), as reported by Stamilla et al [ 18 , 19 ]. Feed texture ranged from finely grounded to crumble in the first 15 days and granulated from day 15 till the end of the cycle.…”
Section: Methodsmentioning
confidence: 99%
“…In-feed inclusion of medium chain fatty acids, together with vaccination of a live attenuated coccidiosis vaccine, reduced necrotic enteritis in broilers [ 22 ]. A microencapsulated blend of organic acids and essential oils could improve the quality and shelf life of poultry meat [ 23 ]. Therefore, acidifiers are promising alternatives to antibiotics for growth performance, antioxidant status, and intestinal health of broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the application of 0.5% microencapsulated OAs (citric and sorbic) with essential oil resulted in less intramuscular fat, lower saturated/polyunsaturated fatty acids ratio, reduced TBARS value, zero contamination of Listeria spp., Campylobacter spp., and Clostridium spp. and increased meat color values than the control treatment [153]. A lower TBARS value influenced the lower lipid oxidation in meat, and prevented the degradation of unsaturated fatty acids, and converted oxymyoglobin to metmyoglobin.…”
Section: Effects Of the Incorporation Of Oas On Meat Preservationmentioning
confidence: 81%
“…Gheisari et al [47] also reported that 0.2% OAs inclusion enhanced the lactobacillus content while reducing the Clostridium perfringens, E. coli, and Salmonella spp content. Moreover, a 0.5% microencapsulated blend of OAs reduced the oxidative status, microbial loads, and improved the shelf life of broiler meat [48]. The protected OAs could be delivered to specific sites in the body and had a positive effect by eliminating the coliforms counts in both the distal jejunum and cecum.…”
Section: Novel Strategies For Enhancing Efficacy Oas Availability In ...mentioning
confidence: 99%